Composition and diversity of ichthyofauna in La Viña reservoir (Córdoba, Argentina) - Mancini,M. (2009)
Several dams have been built in central and north Argentina. There are more than 20 reservoirs in Córdoba province, with a total estimated surface area of around 15,000 ha. Although construction of dams continues, some aspects about the richness, abundance and diversity of ichthyofauna in many of these environments are unknown, which prevents adequate management of fish resources. The goal of this work was to evaluate specific richness and diversity of ichthyofauna in La Viña reservoir (31° 47' S and 65° 01' W, 1,050 ha, 846 m asl), one of the major reservoirs in Córdoba. Fifteen seasonal samplings were made in 1999-2002 using trawl nets and gillnets. A total of 3,242 specimens belonging to 7 species distributed in 5 orders and 5 families were caught. The tetra Astyanax eigenmanniorum (52.9%) and the silverside Odontesthes bonariensis (29.3%) were the most abundant species; the latter is the main target species for lake fishing and had greatest biomass (63.8%). Average diversity for all samples was H'T = 1.63 (95% confidence interval 1.49 to 1.77). Shannon-Wiener and Simpson diversity indexes values were generally intermediate. Specific richness of La Viña reservoir was moderate compared with other impoundments in central and north Argentina.